Synthesis of LiFePO4 in an Open-air Environment. (31st January 2017) - Gu, Fei; Jung, Kichang; Lim, Taehoon; Martinez-Morales, Alfredo A.
ABSTRACT: Among different efforts to increase the competitiveness of lithium-ion batteries (LIBs) in the energy storage marketplace, reducing the cost of production is a major effort by the LIB industry. This work proposes a synthesis method to decrease the production cost for LiFePO4, by synthesizing the material through an open-air environment solid state reaction. The lithium (Li)-ion battery is a member of the family of rechargeable batteries. In our approach, iron phosphate (FePO4 ) powder is preheated to eliminate moisture. Once dried, the FePO4 is mixed with lithium acetate (CH3 COOLi), and the mixture is heated in a tube furnace. The solid-state reaction is conducted in an open-air environment. In order to minimize the oxidation of the formed LiFePO4, a modified tube reaction vessel is utilized during synthesis. X-ray Diffraction (XRD) and Energy Dispersive Spectroscopy (EDS) are used to characterize the crystal structure and chemical composition of the synthesized material. Furthermore, scanning electron microscopy (SEM) characterization shows the grain size of the formed LiFePO4 to be in the range of 200 nm to 600 nm. Cycling testing of fabricated battery cells using the synthesized LiFePO4 is done using an Arbin Tester.